A critical view of the German procurement process in the public sector - Hofacker, Alexander; Santos, Aguinaldo dos; Santos, Adriana de Paula Lacerda (Ambiente Construído, 2012)
This paper makes a critical analysis of the German procurement process in the public sector, based on a case study carried out at Karlsruhe University. The research protocol for the field study was developed in three phases: direct dialogue with the head of the department, document analysis, and semi-structured interviews. Data collection was concerned with both the analysis of the organization as well as with the mapping of project activities. A detailed study was carried out on a single construction project in order to enable the development of a value stream map of the procurement macro processes. Based on the data, the authors present a set of proposals for a radical improvement in the German procurement process, focusing on shortening the cycle time, increasing transparency and improving value generation. The study reinforces the need for more research focused on lean production concepts and principles in the public sector. By identifying radical improvement opportunities in the German procurement process, it may be possible to convince politicians and decision makers to change structures of responsibilities and to apply lean principles in public administration. The paper appears to be one of the first studies to apply lean principles into the procurement process of governmental organizations, in order to simplify processes, reduce waste and better allocate resources in order to add more value for the end-users.